2010
DOI: 10.2174/156652410791317057
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mistletoe Therapy: Friend or Foe in Established Anti-Tumor Protocols? A Multicenter, Controlled, Retrospective Pharmaco-Epidemiological Study in Pancreas Cancer

Abstract: Mistletoe is often used as complementary therapy in oncology. The anti-tumor effects of mistletoe (Iscador) are well documented in-vitro in respect to inhibition of cell proliferation, induction of apoptosis, segmental activation of immune competent cells and trapping of chemotherapeutic drugs within cancer cells by modulating the inhibitory potential of P-glycoprotein (P-gp)-mediated transport of cell toxifying substances (cytotoxic drugs). However, the clinical activity of mistletoe treatment remains still c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 32 publications
3
45
0
1
Order By: Relevance
“…Finally, the adjunctive treatment with mistletoe extracts might have contributed to the favorable outcome of this patient. In line with this, previous smaller-scale studies have suggested a potential benefit of such treatment in patients with various tumorentities,includingbreastcancerandgallbladdercancer [5,6].Thepotentialmechanismsbywhichmistletoeextracts may exert their antiproliferative activity have not yet been exploredindetail [7][8][9],butrecentstudieshavesuggestedan activationofdendriticcells,whichmayfacilitateantitumoral immune responses [10]. Whether mistletoe extracts exert …”
Section: Discussionmentioning
confidence: 94%
“…Finally, the adjunctive treatment with mistletoe extracts might have contributed to the favorable outcome of this patient. In line with this, previous smaller-scale studies have suggested a potential benefit of such treatment in patients with various tumorentities,includingbreastcancerandgallbladdercancer [5,6].Thepotentialmechanismsbywhichmistletoeextracts may exert their antiproliferative activity have not yet been exploredindetail [7][8][9],butrecentstudieshavesuggestedan activationofdendriticcells,whichmayfacilitateantitumoral immune responses [10]. Whether mistletoe extracts exert …”
Section: Discussionmentioning
confidence: 94%
“…86 Recent studies have indicated a possible influence of mistletoe on survival in patients with colorectal or pancreatic carcinomas. 87,88 Matthes et al 87 demonstrated a lower adjusted hazard ratio of dying in patients with pancreatic carcinoma with subcutaneous mistletoe therapy combined with gemcitabine versus the control group who received gemcitabine alone. 80 A randomized controlled trial yielded prolonged survival from 2.7 to 4.8 months in patients with advanced pancreatic cancer not eligible for antineoplastic therapies who were treated with subcutaneous mistletoe in comparison to best supportive care.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in a large retrospective study of mistletoe therapy in nonmetastatic breast cancer patients, fewer adverse events and longer survival were observed in the mistletoe therapy group compared to conventional therapy alone [32]. In a comparable retrospective study design in pancreatic cancer patients, similar clinical outcomes were observed with fewer adverse events and improved survival in patients treated with mistletoe [33]. Despite compelling preclinical data and these isolated reports of clinical benefit of mistletoe preparations, recent reviews of clinical trials still note methodological weaknesses of current published studies on mistletoe [34] as well as conflicting results on tumor response and survival prolongation on treatment using various mistletoe preparations [35][36][37][38].…”
Section: Introductionmentioning
confidence: 94%